On the experience of the urban landscape: A commentary on Siegfried Lenz’s "Von der Wirkung der Landschaft auf den Menschen" - Szczepański, Piotr (Polskie Studia Krajobrazowe, 2019)
The aim of this paper is to characterize the relation between the urban  landscape (the image of the city) and the subject. The landscape is understood here in two ways: as something alien, excluding, and hostile, but also as something that gains new features when in contact with the Other. For it can be said, paraphrasing Siegfried Lenz’s famous statement on the relation between man and landscape, that the city is being created through us. The relationship between the residents and the urban landscape has a reciprocal character, in which “I” places itself in relation to a certain “you.”